2010
DOI: 10.1164/rccm.200907-1141oc
|View full text |Cite
|
Sign up to set email alerts
|

Patient Outcomes after Acute Pulmonary Embolism

Abstract: The clinical course of acute PE is complicated by high rates of serious adverse events, which occur in half of the patients within 4 years.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
31
0
5

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 143 publications
(38 citation statements)
references
References 30 publications
2
31
0
5
Order By: Relevance
“…Not surprisingly, active cancer was the major predictor of death after acute PE during the follow-up period, which is consistent with earlier studies [17, 18]; however, CrCl and eGFR retained significance when cancer was considered in multivariate analysis. Patients with CrCl < 60 mL/min had up to 21-fold and 8-fold elevated risk of death during the 90-day and 1-year follow-up period, respectively.…”
Section: Discussionsupporting
confidence: 90%
“…Not surprisingly, active cancer was the major predictor of death after acute PE during the follow-up period, which is consistent with earlier studies [17, 18]; however, CrCl and eGFR retained significance when cancer was considered in multivariate analysis. Patients with CrCl < 60 mL/min had up to 21-fold and 8-fold elevated risk of death during the 90-day and 1-year follow-up period, respectively.…”
Section: Discussionsupporting
confidence: 90%
“…These illnesses have previously been found to be important baseline characteristics of patients presenting with venous thromboembolism [1,18] and were predictors of long-term survival [1]. In addition to these chronic diseases, Heit et al [1] also reported increasing age, smoking status, chronic renal disease and neurologic disease to be independent predictors of long-term survival in their large inception cohort of patients suffering from venous thromboembolism.…”
Section: Discussionmentioning
confidence: 99%
“…With greater awareness of the disease, it is being more widely recognized, with estimates following an episode of acute pulmonary embolus ranging from 0.8 to 8% in autopsy series, US healthcare insurance databases, and retrospective and prospective studies [5-10]. To put this into perspective, this would mean a prevalence of between 11 and 109 per million cases.…”
Section: Introductionmentioning
confidence: 99%